Patients From Socioeconomically Distressed Communities Experience Similar Clinical Improvements Following Anterior Cervical Discectomy and Fusion. Issue 24 (15th December 2022) - Lambrechts, Mark J.; Toci, Gregory R.; Issa, Tariq Z.; Siegel, Nicholas S.; O'Connor, Patrick; Siniakowicz, Claudia; Syal, Amit; Weber, Jackson; Lawall, Charles; Brush, Parker; Canseco, Jose A.; Kaye, Ian D.; et al.
Abstract : Study Design: Retrospective cohort. Objectives: The aim was to compare patient-reported outcome measures (PROMs) following anterior cervical discectomy and fusion (ACDF) when categorizing patients based on socioeconomic status. Secondarily, we sought to compare PROMs based on race. Summary of Background Data: Social determinants of health are believed to affect outcomes following spine surgery, but there is limited literature on how combined socioeconomic status metrics affect PROMs following ACDF. Materials and Methods: The authors identified patients who underwent primary elective one-level to four-level ACDF from 2014 to 2020. Patients were grouped based on their distressed community index (DCI) quintile (Distressed, At-Risk, Mid-tier, Comfortable, and Prosperous) and then race (White or Black). Multivariate regression for ∆PROMs was performed based on DCI group and race while controlling for baseline demographics and surgical characteristics. Results: Of 1204 patients included in the study, all DCI groups improved across all PROMs, except mental health component score (MCS-12) for the Mid-tier group ( P =0.091). Patients in the Distressed/At-Risk group had worse baseline MCS-12, visual analog scale (VAS) Neck, and neck disability index (NDI). There were no differences in magnitude of improvement between DCI groups. Black patients had significantly worse baseline VAS Neck ( P =0.002) and Arm ( P =0.012) as well as worse postoperative MCS-12 ( P =0.016), PCS-12 ( P =0.03), VAS Neck ( P <0.001), VAS Arm ( P =0.004), and NDI ( P <0.001). Multivariable regression analysis did not identify any of the DCI groupings to be significant independent predictors of ∆PROMs, but being White was an independent predictor of greater improvement in ∆PCS-12 (β=3.09, P =0.036) and ∆NDI (β=−7.32, P =0.003). Conclusions: All patients experienced clinical improvements regardless of DCI or race despite patients in Distressed communities and Black patients having worse preoperative PROMs. Being from a distressed community was not an independent predictor of worse improvement in any PROMs, but Black patients had worse improvement in NDI compared with White patients. Level of Evidence: 3.